Dynamics of germination of vegetable seeds when using dimethyl (1-hydroxy-1-phenylethyl) phosphanate as an accelerator - Gaukhar Baitasheva; Aitzhamal Mussina; Galiya Medeuova; Akbota Kuandykova; Elmira Imanova; Akmaral Sartayeva; Karlygash Zhamanbayeva; Ayaulym Umbetulla (Caspian Journal of Environmental Sciences)
This study examines the effects of dimethyl (1-hydroxy-1-phenylethyl) phosphonate as a germination accelerator on various vegetable seeds. Seed germination is a critical phase in plant growth, significantly influencing crop yield and quality. The primary objective was to determine the compound's efficacy in enhancing germination rates and vigor by monitoring key indicators such as germination percentage, speed, and seedling development. A range of concentrations was tested to identify optimal dosages and effects. Results indicated that dimethyl (1-hydroxy-1-phenylethyl) phosphonate, at specific concentrations, significantly improved germination speed and uniformity, with enhanced early growth metrics compared to untreated controls. The findings suggest that this compound may be an effective germination promoter in agricultural applications, potentially reducing germination time and improving crop establishment under diverse conditions.